Mental health as a dimension for the care of teenagers - Rosália Teixeira Luz; Edméia de Almeida Cardoso Coelho; Marizete Argolo Teixeira; Andiara Rodrigues Barros; Maria de Fátima Alves Aguiar Carvalho; Mariza Silva Almeida
ABSTRACT Objective: To analyze the demands in the field of mental health from the perspective of teenagers. Method: A descriptive study with a qualitative approach, having comprehensiveness as an analytical category. It was carried out with 21 teenagers of both genders, students of two public schools of a municipality of the countryside of Bahia state. The empirical material was produced through reflection workshops and analyzed through the technique of Discourse Analysis. Results: Teenagers value the indissociability between body and mind, recognize lack of attention to the psychological dimension in the health network, and point to mental disorders as resulting from contexts of life and lack of Health Care. Conclusion: Health services need to be structured to attract teenagers, to recognize singularities through professionals trained in welcoming, listening and accountability. It is urgent to fulfill what is defined in public policies and in specific programs, and that comprehensiveness has a centrality as a perspective to be realized.